Evaluation of mercury levels in hair of children resident in artisanal gold mining area in the city of Chapada de Natividade - Tocantins - Seyna Ueno Rabelo Mendes; Marina Beatriz Agostini Vasconcellos; Marilia Gabriela Miranda Catharino; Gilson Alves Quinaglia; Barbara Held (Brazilian Journal of Radiation Sciences)
ABSTRACT